Mechanical Properties of Randomly Oriented Calotropis Gigantea Fiber-Reinforced Phenol Formaldehyde Biocomposites - Athijayamani, A.; Sekar, S.; Sidhardhan, S.; Ramanathan, K. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Mechanical properties such as tensile, flexural and impact, of randomly oriented Calotropis Gigantea Fiber (CGF) -reinforced Phenol Formaldehyde (PF) biocomposites were studied based on the five different fiber loadings (10, 20, 30, 40, and 50 vol%) and three different fiber lengths (3, 9, and 15 mm). The critical fiber length and optimum fiber loading were identified with the maximum level of mechanical properties in this composite. The fractured surfaces of composites after testing were studied by scanning electron microscope (SEM). The results revealed that the addition of CGFs is improving the mechanical properties of the PF composite. The properties of composites reach the properties of the neat resin sample at 20 vol% of all the cases. The critical fiber length and the optimum fiber loading to obtain the maximum mechanical properties were identified as 9 mm and 40 vol% respectively. Experimental tensile property values were compared with theoretical values and found to be in good agreement.